The mechanical behavior of dentin: importance of microstructure, chemical composition and aging (2017)
Dental fracture is one of the three most common forms of failure of restored teeth and the most common cause of tooth loss or extraction in elderly patients -- Previous investigations conducted on aging of hard tissues have identified that there is a considerable reduction in the mechanical properties (i.e. fracture toughness, fatigue and flexural resistance) of dentin with aging and that may predispose tooth fracture -- These declines in properties have been attributed to microstructural and chemical composition changes over time -- However, these aging processes have not been really quantified and related with the changes in mechanical properties -- Accordingly, the aim of this work is to evaluate the aging process of coronal dentin in terms of the evolution of microstructure, changes in chemical composition and mechanical properties from selected age groups (young and old donors) -- The changes in these properties were evaluated in three different regions (outer, middle and inner) in order to identify spatial variations within the crown -- A brief description of the main literature on composition, microstructure and mechanical behavior of dentin is presented in chapter 2 -- An extensive experimental study was carried out in chapter 3 to identify the changes in microstructure of dentin with aging by means of optical and electron microscopy; while changes in chemical composition were analyzed using Raman Spectroscopy to calculate the mineral-to-collagen ratio -- Changes in mechanical properties were measured using Vickers micro-hardness -- Chapter 4 describes the importance of tubule density to the fracture toughness of dentin for young and old donor’s groups -- An approach previously proposed to study the mechanical behavior of porous materials was used to model the fracture toughness of coronal dentin in terms of the tubule characteristics -- Results were then compared with published results from previous studies -- The time-dependent deformation response of dentin was analyzed via spherical indentation experiments at different indentation loads in Chapter 5 -- From the experimental observations was proposed a simple model to describe the time dependent deformation behavior of dentin -- This model was based on previously proposed theories for indentation of time dependent materials, showing that the effective strain rate of dentin depends on its chemical composition (i.e. mineral-to-collagen ratio) and microstructure (i.e. lumen area fraction) -- The descriptions of the model were compared with the experimental results showing good agreement -- The same model was validated with experimental results of aged dentin, finding a low change in the deformation response of dentin with aging, as presented in chapter 6 -- Finally, preliminary results made on the mechanical properties of dentin have shown that the microstructure of aged human dentin can vary depending on the ethnic background of the donor and that this quality is critically important to the mechanical properties of the tissue -- In chapter 7 preliminary results on the comparison between the microstructure, chemical composition and mechanical properties of Colombian, Chinese and American donors is presented -- Finally, conclusions for the study are presented in chapter 8